Impact of the number of blades of the geokhod cutting body on cutting forces - Aksenov V. V. Vladimir Valerievich; Sadovets V. Yu. Vladimir Yurievich; Rezanova E. V. Elena Viktorovna; Pashkov D. A. Dmitry Alekseevich (2017, 2017)
Title screen